2019
DOI: 10.1002/asl.906
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of cloud vertical structure in three reanalyses against CloudSat/cloud‐aerosol lidar and infrared pathfinder satellite observations

Abstract: Cloud fraction is a great source of uncertainty in current models. By utilizing cloudiness fields from CloudSat/cloud-aerosol lidar and infrared pathfinder satellite observations (CALIPSO), the three widely used reanalyses including the Interim ECWMF Re-Analysis (ERA-Interim), Japanese 55-yar Reanalysis (JRA-55), and the Modern-Era Retrospective Analysis for Research and Applications (MERRA-2) are assessed for their representation of cloudiness. Results show all three reanalyses can basically capture the cloud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…Since 2006, with the launch of the CloudSat and CALIPSO satellites, the vertical structure of clouds and their radiative effects over the TP have been the focus of considerable research interest [ 130 , 131 ]. However, current climate models and even reanalysis systems still cannot simulate adequately the vertical structure of clouds [ 132 ]. To improve simulations of clouds and precipitation over the TP, additional efforts are required to reveal the roles of the physical processes of both the planetary boundary layer and the underlying surface of the TP in shaping shallow and deep convective clouds.…”
Section: Prospectsmentioning
confidence: 99%
“…Since 2006, with the launch of the CloudSat and CALIPSO satellites, the vertical structure of clouds and their radiative effects over the TP have been the focus of considerable research interest [ 130 , 131 ]. However, current climate models and even reanalysis systems still cannot simulate adequately the vertical structure of clouds [ 132 ]. To improve simulations of clouds and precipitation over the TP, additional efforts are required to reveal the roles of the physical processes of both the planetary boundary layer and the underlying surface of the TP in shaping shallow and deep convective clouds.…”
Section: Prospectsmentioning
confidence: 99%
“…The accuracy of the shortwave radiation variable from the MERRA-2 product over Africa was recently evaluated against four ground stations in Ethiopia by Stettz et al (2019), who reported a good agreement between the climate reanalysis data and the observed data. Miao et al (2019) compared the cloud cover of MERRA-2 with Cloud-Sat/CALIPSO data, showing that the MERRA-2 underestimates the cloud cover for the ZRB region by a maximum of 10%. Torralba et al (2017) compared the wind speed trends from MERRA-2 and JRA-55 climate reanalysis products, concluding that the two products yield similar trends, thus suggesting MERRA-2 to be a good data source to evaluate the wind speed at 850 hPa.…”
Section: Present Climate Datamentioning
confidence: 99%
“…Miao et al . (2019) compared the cloud cover of MERRA‐2 with Cloud‐Sat/CALIPSO data, showing that the MERRA‐2 underestimates the cloud cover for the ZRB region by a maximum of 10%. Torralba et al .…”
Section: Datamentioning
confidence: 99%
“…Previous studies have evaluated the cloud amount in reanalysis datasets using ground‐based remote sensing cloud data or satellite cloud data (Bedacht et al., 2010; Chevallier et al., 2005; Jakob, 1997; Naud et al., 2014; Yousef et al., 2020). Miao and Wang (2019) assessed the cloud products of three widely‐used reanalysis data sets, ERA‐Interim, JRA‐55 and MERRA‐2, based on Cloudsat/CALIPSO (Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observations). It was found that ERA‐Interim is closest to CloudSat/CALIPSO, but shows considerable underestimation for high clouds.…”
Section: Introductionmentioning
confidence: 99%